Blood–cerebrospinal fluid barrier: another site disrupted during experimental cerebral malaria caused by Plasmodium berghei ANKA - Ngo-Thanh, Ha; Sasaki, Tsutomu; Suzue, Kazutomo; Yokoo, Hideaki; Isoda, Koji; Kamitani, Wataru; Shimokawa, Chikako; Hisaeda, Hajime; Imai, Takashi (International journal for parasitology, 2020)
[Display omitted] •A new method to evaluate the integrity of the blood–cerebrospinal fluid barrier (BCSFB) was developed.•BCSFB permeability was increased specifically in cerebral malaria (CM), but not in non-CM.•CD8+ T cells are involved in the BCSFB breakdown during CM.•Hemozoin was found in the choroid plexus in CM. Cerebral malaria is one of the most severe pathologies of malaria; it induces neuro-cognitive sequelae and has a high mortality rate. Although many factors involved in the development of cerebral malaria have been discovered, its pathogenic mechanisms are still not completely understood. Most studies on cerebral malaria have focused on the blood–brain barrier, despite the importance of the blood–cerebrospinal fluid barrier, which protects the brain from peripheral inflammation. Consequently, the pathological role of the blood–cerebrospinal fluid barrier in cerebral malaria is currently unknown. To examine the status of the blood–cerebrospinal fluid barrier in cerebral malaria and malaria without this pathology (non-cerebral malaria), we developed a new method for evaluating the permeabilization of the blood–cerebrospinal fluid barrier during cerebral malaria in mice, using Evans blue dye and a software-assisted image analysis. Using C57BL/6J (B6) mice infected with Plasmodium berghei ANKA strain as an experimental cerebral malaria model and B6 mice infected with P. berghei NK65 strain or Plasmodium yoelii as non-cerebral malaria models, we revealed that the permeability of the blood–cerebrospinal fluid barrier increased during experimental cerebral malaria but not during non-cerebral malaria. We observed haemorrhaging in the cerebral ventricles and hemozoin-like structures in the choroid plexus, which is a key component of the blood–cerebrospinal fluid barrier, in cerebral malaria mice. Taken together, this evidence indicates that the blood–cerebrospinal fluid barrier is disrupted in experimental cerebral malaria, whereas it remains intact in non-cerebral malaria. We also found that P. berghei ANKA parasites and CD8+ T cells are involved in the blood–cerebrospinal fluid barrier disruption in experimental cerebral malaria. An understanding of the mechanisms underlying cerebral malaria might help in the development of effective strategies to prevent and manage cerebral malaria in humans.